Study of ethnography and character education values at the Situntun pencak silat college - Luh Made Widhi Rusmaladewi; I Ketut Budaya Astra; I Gede Suwiwa (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
This study discusses ethnography and the values of character education at the Situntun Pencak Silat College in Banjar Village, Banjar District, Buleleng Regency. The Situntun Pencak Silat College is a long-established college, this makes the Situntun Pencak Silat College also known as the Traditional Pencak Silat College. However, until now there is no valid documentation and information from the pencak silat school of Situtun, so many people do not know about the existence of the Pencak Silat School of Situtun. This study aims to determine the existence of the pencak silat school of Situtun and its character education values so that it can publish or disseminate information and documents related to the Pencak Silat School of Situtun. This study uses a qualitative research method with an ethnographic approach and uses interview techniques to collect data. The discussion in this article includes knowledge of the history of the Situntun Pencak Silat College from its inception, the ethnography of the Situntun Pencak Silat College, and the values of character education contained and applied to the Situntun Pencak Silat College. The results showed that the Situtun Pencak Silat College was founded in 1879 until now. Situntun pencak silat college has spread to villages and banjar villages. The values of character education have also been instilled since the beginning of the fighter starting practice. The school of pencak silat situntun is less active and even begins to dim and many people do not know about the existence of the pencak silat school of situtun. This study was conducted to determine the profile and character education of the Situtun Pencak Silat College. With this research, the martial arts college of Situtun can be known by many people. The results of this study can be used as study material to explore the ethnography of the Situntun pencak silat college, especially for the community in the village of Banjar Buleleng, and increase the character education values of the Situtun pencak silat school fighter.